Investigation of fungicidal activity of nanoparticles ZnO, TiO2 AND Ag0 of different size - Pasichnyk, Maria (ScienceRise: Biological Science, 2019)
The paper presents studies on the determination of fungicidal properties of colloidal solutions of various sizes of ZnO, TiO2 and Ag0 nanoparticles. The aim of the study was to determine the effect of ZnO, TiO2 and Ag0 nanoparticles on their fungicidal activity. Materials and methods. In order to achieve this goal in the article, studies were conducted to determine the fungicidal activity of different sizes of ZnO, TiO2 and Ag0 nanoparticles. Also, the percentage of fungicidal effectiveness of using colloidal solutions of nanowires ZnO, TiO2 and Ag0 of various sizes is estimated. Fungicidal properties of nanosolutions were evaluated in the form of fungicidal activity and fungicidal efficacy. Fungicidal activity and fungicidal efficacy of colloidal solutions were investigated by the visual evaluation method for mold fungi of the genus Aspergillus (black mold or dark gray mold) and fungi of genus Penicillium (blue-green mold) that form colonies on rye-wheat bread. Results. A correlation between sizes of nanoparticles of ZnO, TiO2 and Ag0 and their fungicidal action has been established. For the study, the prepared aqueous solutions of ZnO and TiO2 nanoparticles at a concentration of 0.5% were 25 nm, 35 nm, 50 nm, and solutions of Ag0 nanoparticles were prepared using OS-20 surfactant and sodium citrate precursor, the sizes of synthesized nanoparticles were 35 nm and 50 nm, the concentration of solutions of nanoparticles Ag0 was 0.5%. The high fungicidal activity was demonstrated by colloid solutions of nanosilver with particles sizes as 50 nm, contained sodium citrate solution, 2 points, contained OS-20 surfactant solution– 3 points. Conclusion. As a result of the studies, a correlation was found between the size of the nanoparticles and their fungicidal activity, so that smaller particles of TiO2 exhibit greater fungicidal activity. ZnO and Ag nanoparticles have more pronounced fungicidal properties in larger sizes